PENGARUH GAYA HIDUP,WORD OF MOUTH DAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK WARDAH DI STORE JS MART DI KETAHUN BENGKULU UTARA - Fitri, Marliza; Fitriana, Meyta Ayu (UM. Bengkulu, 2024)
This study aims to determine the influence of lifestyle , word of mouth and advertising on the decision to purchase wardah products at the JS Mart store in Ketahun , North Bengkulu . The method used is quantitative method. Methods of data collection by questionnaire Sampling using the Simple Random Sampling method, with a total of 85 respondents. This researcher uses multiple regression analysis. The results of research that has been done on the influence of lifestyle, word of mouth and advertising on purchasing decisions for wardah products at the JS Mart store in Ketahun, North Bengkulu. The correlation coefficient test can be assessed as R = 0.890 and (X2) and advertising (X3) contributes an influence of 0.792 or 79.2% to the purchase decision (Y) on wardah products at JS Mart Ketahun North Bengkulu. While the remaining 0.208 or 20.8% is influenced by other variables not included in this study. Keywords: Purchase Decision, Lifestyle, Word Of Mouth End Advertisting